2021
DOI: 10.22146/majkedgiind.44383
|View full text |Cite
|
Sign up to set email alerts
|

The retention difference between cobalt chromium and zirconia coping in different angulations on telescopic overdenture

Abstract: Telescopic overdenture is one type of removable denture that uses dual coping system that consists of primary and secondary coping. Retention of telescopic overdenture is obtained from the friction between primary and secondary coping, which is mainly influenced by the type of material and coping angulation. The purpose of this study is to determine the retention differences between CoCr and zirconia coping with 0°, 1°, and 2° angulations. Twenty four pairs of telescopic overdenture coping samples with 6 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…After 50,000 cycles of the CS representing 3 months of function of RPD, the results showed that the decrease in the retention values was higher in Group II (cobalt-chromium) compared to Group I (zirconia group). This may have resulted from the lower surface roughness of the Zirconia copings than CoCr copings; thus, zirconia copings have a wider contact area or dry friction (FD) [47]. This is consistent with the previous studies which reported that the amount of retention or friction between primary and secondary copings of telescopic over-dentures mostly results from FD, lubricated friction, and boundary friction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After 50,000 cycles of the CS representing 3 months of function of RPD, the results showed that the decrease in the retention values was higher in Group II (cobalt-chromium) compared to Group I (zirconia group). This may have resulted from the lower surface roughness of the Zirconia copings than CoCr copings; thus, zirconia copings have a wider contact area or dry friction (FD) [47]. This is consistent with the previous studies which reported that the amount of retention or friction between primary and secondary copings of telescopic over-dentures mostly results from FD, lubricated friction, and boundary friction.…”
Section: Discussionsupporting
confidence: 89%
“…These three types of frictions can occur when the secondary internal surface coping moves into the loose direction of the primary polishing surface coping. Out of these frictions, FD has the strongest influence since wider contact area between copings will result in greater retention [47], [48]. It was found that irrespective of the measurement stage, the difference between both groups was statistically significant.…”
Section: Discussionmentioning
confidence: 93%